Analysis of System Performance Using VMware ESXi Server Virtual Machines - Hiteshi (My University, 2012)
Virtualization refers to the abstraction of computer resources. The main purpose of virtual environment is to improve resource utilization by consolidating the operating platforms for users and applications. Recently, virtualization at all levels i.e. system, storage, and network; becomes important as a way to improve system security, reliability, reduce costs and provide greater flexibility. System-level virtualization has been regained popularity during the past few years because of the availability of efficient solution such as Xen, VMware, Hyper-V and the implementation of hardware support in processors (e.g. Intel-VT, AMD-V). By interpreting the machine, one is able to run a variety of operating systems and environments as needed by the applications. Virtualization allows users to isolate workloads, improving security and reliability and also possible to balance workloads, use migration techniques to relocate applications from failing machines, and isolate fault systems for repair. This thesis work presents an efficient implementation of a system-level performance using virtual machine hypervisor VMware ESXi server. This technique allows collection of essential workload characteristics for arbitrary and unmodified operating system instances running in virtual machines. For capturing the result efficiently, a command line interface is used which encompasses essential performance metrics including memory usage, CPU usage, disk usage and overall system usage, which further can be represent graphically using esxplot tool. The demonstration of technique can be done by using a benchmark tool to generate workload.
M.E. (Software Engineering)
Keywords: Virtual Machines